Characteristics of sago pith and sago bark waste from Seram Island, Maluku, Indonesia - Herman Siruru; WASRIN SYAFII; I NYOMAN J. WISTARA; GUSTAN PARI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Siruru H, Syafii W, Wistara I. N. J, Pari G. 2019. Characteristics of Metroxylon rumphii (pith and bark waste) from Seram Island, Maluku, Indonesia. Biodiversitas 20: 3517-3526. Sago (Metroxylon rumphii Martius) pith waste (SPW) and sago bark waste (SBW) are lignocellulosic materials that can be used for various needs directly or indirectly. It is necessary to understand SPW and SBW characteristics to maximize their utilization. In this study, we analyzed the proximate, ultimate, and crystallinity by XRD, the functional groups by FTIR, morphology by SEM, and the derivate analysis of hot water-soluble extractives by GCMS. The contents of SPW and SBW hot-water soluble extractive, lignin, and holocellulose were 57.7 and 4.9%, 6.1 and 29.4%, and 45.74 and 66.74%, respectively. The volatile matter, ash content, silica, fixed carbon, C, H, and O contents of the SPW and SBW were 81.48 and 84.56%, 1.30 and 3.04%, 1.25% and 2.03, 12.77 and 18.06%, 37.93 and 44.64%, 6.37 and 6.49%, and 47.75 and 51.10%, respectively. The degree of crystallinity of SPW was 15.04%, while that of SBW was 47.28%, where both have a monoclinic structure with the main peak by 2? 16° and 26°. SPW and SBW contained several minerals such as silica, boron, sulfur, and phosphorus. The surface morphology of the SPW was porous with a small diameter and thin cell wall, while that of SBW was covered by minerals. Nitrogen, alcohol, and sugar group compounds were found more in SPW, whereas phenol compound was more in SBW. SBW has high lignin content and SPW has a very large amount of hot water-soluble extractive.